Diacerein: A potential multi-target therapeutic drug for COVID-19 (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 19 (COVID19), was declared pandemic by the World Health Organization in March 2020. SARS-CoV-2 binds its host cell receptor, angiotensin-converting enzyme 2 (ACE2), through the viral spike (S) protein. The mortality related to severe acute respiratory distress syndrome (ARDS) and multi-organ failure in COVID-19 patients has been suggested to be connected with cytokine storm syndrome (CSS), an excessive immune response that severely damages healthy lung tissue. In addition, cardiac symptoms, including fulminant myocarditis, are frequent in patients in a severe state of illness. Diacerein (DAR) is an anthraquinone derivative drug whose active metabolite is rhein. Different studies have shown that this compound inhibits the IL-1, IL-2, IL-6, IL-8, IL-12, IL-18, TNF-α, NF-κB and NALP3 inflammasome pathways. The antiviral activity of rhein has also been documented. This metabolite prevents hepatitis B virus (HBV) replication and influenza A virus (IAV) adsorption and replication through mechanisms involving regulation of oxidative stress and alterations of the TLR4, Akt, MAPK, and NF-κB signalling pathways. Importantly, rhein inhibits the interaction between the SARS-CoV S protein and ACE2 in a dose-dependent manner, suggesting rhein as a potential therapeutic agent for the treatment of SARS-CoV infection. Based on these findings, we hypothesize that DAR is a multi-target drug useful for COVID-19 treatment. This anthraquinone may control hyperinflammatory conditions by multi-faceted cytokine inhibition and by reducing viral infection.